Global trends in the formation of professors - ABDELHAFID, Zinabeddine (Social Sciences Journal)
The development of any community is ,undoubtedly, related strongly to the quality of its educational system,and that happens through its effective contributions to prepare people to bear responsibilities which, in turn,leads to the development of communities in different fields.Therefore,different countries sought to develop the infrastructures represented by the educational organizations in which people can have the opportunity to receive their training and preparation ,and since the teacher is the corner stone of the educational system,they also sought to train and prepare him through different training programmes relative to the cognitive,cultural and educational aspects. the growing number of research in the educational field, has lead to the appearance of the diversity of the international trends intended for teacher preparation, in addition to the diversity of the related programmes.This study aims at mentioning the most eminent trends , teacher preparation programmes and their related systems